Pt Kereta Api Indonesia (Persero) Strategy in Facing Corona Virus Disease-19 Pandemic - Ambar Mutiara; Djoko Suhardjanto; Yeni Priatna Sari (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this research is to study and find out the strategies implemented by KAI in dealing with theimpact of the Covid-19 pandemic on KAI’s performance. The method of analysis in this study is a qualitativedescriptive method by analyzing all the data related to the topic being studied, which is then presentedwith fairly comprehensive and comprehensive arguments. The results showed that the very fast growth inthe last ten years is KAI’s performance that should be appreciated. However, the Covid-19 pandemic is areminder that economic development (profit) must be accompanied by the principles of sustainability andenvironmental and social concerns. The current situation in the impact of the Covid-19 Pandemic is veryunfavorable for achieving revenue targets for passenger and freight transport. KAI has carried out variousstrategies in dealing with the impact of the Covid-19 pandemic. Several things that have been done by KAIin dealing with the impact of the Covid-19 pandemic include: 1. Protecting passengers and employees ofKAI by prioritizing health through the Covid-19 prevention protocol; 2. Maintain company liquidity bypreparing several scenarios, if the pandemic ends in June, August or December; 3. Perform cost efficiency(operational expenditure) and reduced investment (capital expenditure) to balance the potential decline inincome.